Effect of interface mobility on coalescence of the dispersed phase domains upon processing of 20/80 EPDM/PP melt blends - I Ster; Yu. P. Miroshnikov (Тонкие химические технологии, 2007)
The effect of crosslink density (Nc) of the inner EPDM rubber phase on the coalescence of its domains during capillary extrusion of 20/80 EPDM/PP blends has been studied. The EPDM phase was preliminary loaded with varying amounts of vulcanization agents followed by the reactive blending with PP matrix on a roll mill at 185 o C. The samples were extruded through a capillary rheometer at 185 o C. It is demonstrated that even at low shear rate the convergent flow results in strong coalescence efficacy of droplets in raw blends and in complete suppression of coalescence at low Nc.